1989
DOI: 10.1083/jcb.108.3.1039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of the 21-kD and 26-kD gap junction proteins in murine liver and cultured hepatocytes.

Abstract: Abstract. Affinity-purified antibodies to mouse liver 26-and 21-kD gap junction proteins have been used to characterize gap junctions in liver and cultured hepatocytes. Both proteins are colocalized in the same gap junction plaques as shown by double immunofluorescence and immunoelectron microscopy. In the lobules of rat liver, the 21-kD immunoreactivity is detected as a gradient of fluorescent spots on apposing plasma membranes, the maximum being in the periportal zone and a faint reaction in the perivenous z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
177
2
3

Year Published

1989
1989
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(192 citation statements)
references
References 29 publications
10
177
2
3
Order By: Relevance
“…An indirect effect of S. aureus on astrocyte Cx26 expression could be envisioned to occur through an autocrine/paracrine action since both TNF-α and IL-1β are capable of activating MAPK pathways upon binding to their cognate receptors (Hanada and Yoshimura, 2002). Since Cx26 is not phosphorylated it is more likely that any indirect effects of proinflammatory stimuli would be exerted at the level of transcription/ translation (Kojima et al, 1999;Saez et al, 1998Saez et al, , 2005Traub et al, 1989). Although Temme et al (1998) have reported that IL-1 and TNF-α augment Cx26 while decreasing Cx32 mRNA expression in hepatocytes, to our knowledge, the role of proinflammatory mediators on modulating Cx26 levels in astrocytes has not yet been examined.…”
Section: Discussionmentioning
confidence: 99%
“…An indirect effect of S. aureus on astrocyte Cx26 expression could be envisioned to occur through an autocrine/paracrine action since both TNF-α and IL-1β are capable of activating MAPK pathways upon binding to their cognate receptors (Hanada and Yoshimura, 2002). Since Cx26 is not phosphorylated it is more likely that any indirect effects of proinflammatory stimuli would be exerted at the level of transcription/ translation (Kojima et al, 1999;Saez et al, 1998Saez et al, , 2005Traub et al, 1989). Although Temme et al (1998) have reported that IL-1 and TNF-α augment Cx26 while decreasing Cx32 mRNA expression in hepatocytes, to our knowledge, the role of proinflammatory mediators on modulating Cx26 levels in astrocytes has not yet been examined.…”
Section: Discussionmentioning
confidence: 99%
“…From a functional perspective, several studies of assembly and regulation of gap junctions comprising Cx43 have emphasized apparent correlates with phosphorylation, 7,22,26,28,[41][42][43][44][45][46][47][48][49] although Cx26, which is capable of forming gap junctions, does not appear to be phosphorylated [50][51][52] ; truncation mutants of Cx43, which lack the phosphorylation sites also form functional channels. [53][54][55][56] Formation of the more highly phosphorylated form of Cx43 appears to correlate with plasma membrane insertion and its assembly into gap junctions, 28,43 although such slower migrating forms can arise under other conditions and initial phosphorylation may occur as early as in the Golgi apparatus.…”
Section: Fig 6 Indirect Immunofluorescence Localization Of E-cadhermentioning
confidence: 99%
“…Unlike most membrane proteins, connexins exhibit an exceptionally high metabolic lability with half-lives ranging from 1.5 to 5 h (8-10). The rapid turnover of connexins has been observed in a wide variety of cultured mammalian cells (10,11), whole organs (12), and intact animals (13). Therefore, an efficient and highly regulated degradation mechanism is necessary to control the dynamic turnover of connexins.…”
mentioning
confidence: 99%